Nursing of a patient undergoing resection for giant abdominal lipomatous tumor (1例非典型脂肪瘤样肿瘤患者行腹部巨大肿瘤切除术后的护理体会) - ZHU Xiaohui (朱晓辉); LI Jingjing (李晶晶); JIA Bo (贾波) (中西医结合护理)
This paper summarized the nursing management of resection for giant abdominal tumor in a patient with lipomatous tumor. Based on the nursing assessment and illness condition monitoring, comprehensive nursing interventions including pain control, nutrition support, health education and psychological care were carried out to relieve the patient’s negative emotion, prevention postoperative complications and improve the recovery. (本文总结1例非典型脂肪瘤样肿瘤患者行腹部巨大肿瘤切除术后的护理经验。患者入院后完善常规检查, 做好术前准备和术中配合, 术后加强病情观察, 针对性止痛, 给予营养支持, 开展健康教育和心理干预, 缓解患者负性情绪, 预防并发症, 促进患者早日康复。)